Social Media Brand Engagement in The Multi-Stakeholder Environment of Higher Education Institutions: The Case of Foundation Universities in Istanbul (Third Sector Social Economic Review, 2025)
The marketization and internationalization of Higher Education Institutions necessitate the use of branding strategies in higher education in developed and developing countries. Social media platforms offer various opportunities for Higher Education Institutions by assisting in the development of institutional brands and the formation and cultivation of relationships with students and other stakeholders that will enable engagement. Rather than taking students and potential students as the major unit of analysis, the present study focuses on how Higher Education Institutions create social media content to enable engagement with different stakeholders in an emerging market. Instagram data was collected for four months from the top twenty foundation universities in Istanbul. The findings provide evidence that Higher Education Institutions use different types of Instagram strategies to contribute and foster a multi-stakeholder engagement creating a student, academic, community or hybrid form of social media engagement. The paper offers several contributions to the brand management literature especially with a focus on Higher Education Institutions branding and managerial implications for Higher Education Institutions that aim to stay competitive in the presence of a multi-stakeholder environment.
Keywords: social media brand engagement; higher education institutions; stakeholders; social media strategies; Instagram